Biosynthetic energy cost for amino acids decreases in cancer evolution - Hong Zhang (Nature Portfolio, 2018)
Proliferating cancer cells have a high demand for amino acids. Here, Zhang et al. show that cancer cells evolve towards gene expression profiles that use amino acids with lower biosynthetic energy costs, and demonstrate the potential prognostic utility of quantifying the extent of this adaptation.